2015
DOI: 10.1155/2015/426069
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Suppresses Cerebral Infarct Volume and Cell Death after Ischemic Injury: Involvement of FOXO3 Inactivation and Bcl2 Expression

Abstract: Ischemic stroke interrupts the flow of blood to the brain and subsequently results in cerebral infarction and neuronal cell death, leading to severe pathophysiology. Glutathione (GSH) is an antioxidant with cellular protective functions, including reactive oxygen species (ROS) scavenging in the brain. In addition, GSH is involved in various cellular survival pathways in response to oxidative stress. In the present study, we examined whether GSH reduces cerebral infarct size after middle cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 75 publications
3
33
0
Order By: Relevance
“…Although there are no previous studies interpreting the effect of CoQ10 on p -FOXO3A, we can assume that CoQ10 induced p -FOXO3A could be attributed to the increased phosphorylation of Akt along with the antioxidant capacity of CoQ10, proven herein and supported by the study of Song et al (2015) . These authors found that administration of GSH attenuate cerebral infarct volume in rats exposed to focal ischemia, improved the survival of brain endothelial cells, and reduced FOXO3A nuclear translocation by promoting PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Although there are no previous studies interpreting the effect of CoQ10 on p -FOXO3A, we can assume that CoQ10 induced p -FOXO3A could be attributed to the increased phosphorylation of Akt along with the antioxidant capacity of CoQ10, proven herein and supported by the study of Song et al (2015) . These authors found that administration of GSH attenuate cerebral infarct volume in rats exposed to focal ischemia, improved the survival of brain endothelial cells, and reduced FOXO3A nuclear translocation by promoting PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 77%
“…To further confirm that increased proliferation of HeLa and IMR90 cells by continuous exposure to an EMF is mainly due to decreased ROS levels, we examined the intracellular ROS-mediated signaling pathways that control cell growth. Several studies have shown that reduced intracellular ROS levels by antioxidants increase phosphorylation of Erk1/2 and Akt [ 28 , 29 ]. Consistent with this, we observed phosphorylation of Akt and Erk1/2 in HeLa and IMR-90 cells exposed to an EMF for 1, 6, 12, and 24 h by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that Akt phosphorylation level is decreased in MnSOD transfected 7721 cells, but is elevated in anti-sense MnSOD transfected ones [19] , [24] . Furthermore, GSH have been reported to activate PI3K/Akt signaling and inhibit the activation of FOXO3 [25] . Our results confirmed that ROS can activate Akt, and demonstrated that ROS-induced telomerase activity may be correlated with Akt activation.…”
Section: Discussionmentioning
confidence: 99%